Local Hemodynamic Forces After Stenting: Implications on Restenosis and Thrombosis. Issue 12 (December 2017) - Ng, Jaryl; Bourantas, Christos V.; Torii, Ryo; Ang, Hui Ying; Tenekecioglu, Erhan; Serruys, Patrick W.; Foin, Nicolas
Abstract : Local hemodynamic forces are well-known to modulate atherosclerotic evolution, which remains one of the largest cause of death worldwide. Percutaneous coronary interventions with stent implantation restores blood flow to the downstream myocardium and is only limited by stent failure caused by restenosis, stent thrombosis, or neoatherosclerosis. Cumulative evidence has shown that local hemodynamic forces affect restenosis and the platelet activation process, modulating the pathophysiological mechanisms that lead to stent failure. This article first covers the pathophysiological mechanisms through which wall shear stress regulates arterial disease formation/neointima proliferation and the role of shear rate on stent thrombosis. Subsequently, the article reviews the current evidence on (1) the implications of stent design on the local hemodynamic forces, and (2) how stent/scaffold expansion can influence local flow, thereby affecting the risk of adverse events.